Excision of Spinal Tumor in a Patient With Severe Pulmonary Dysfunction Using Combined Spinal and Epidural Anesthesia With Two Epidural Catheters. Issue 3 (1st May 1999) - Takiguchi, Tetsuo; Okano, Takatoshi; Okuda, Yasuhisa; Kitajima, Toshimitsu
Abstract : Background and Objectives: Combined spinal and epidural anesthesia (CSEA) has become common practice. We performed CSEA using two epidural catheters in a 69-year-old female with severe pulmonary dysfunction caused by a diaphragmatic hernia, who underwent surgical excision of a lumbar spinal tumor. Methods: Combined spinal and epidural anesthesia was performed using two epidural catheters to minimize postoperative pulmonary complications. One epidural catheter was inserted above the surgical region, at the T11-12 interspace, and another one below the surgical region, via the sacral hiatus. Spinal anesthesia was produced using the L5-S1 interspace and 3 mL 0.5% bupivacaine. Oxygen, 3 L/min, was administered through a face mask during surgery. Results: Fifteen minutes after spinal anesthesia, analgesic level was confirmed below T7 using the pinprick method. The patient complained of pain in the surgical region 10 minutes after the dura mater was opened. We injected 5 mL 2% mepivacaine through the upper epidural catheter to relieve the pain. We also injected 10 mL 2% mepivacaine through the lower catheter when she felt pain in the right leg. The perioperative course was uneventful. Oxygen saturation was maintained above 95%. Conclusions: Combined spinal and epidural anesthesia using two epidural catheters was used successfully to excise a spinal tumor in a patient with severe pulmonary dysfunction.